Effect of Nano‐Copper Chromite on the Thermal Decomposition and Combustion of AP‐Based Solid Propellants. Issue 10 (9th August 2022) - Gou, Bingwang; Kou, Yong; Hu, Yubing; Zhang, Guangpu; Guo, Hu; Xiao, Lei; Zhao, Fengqi; Gao, Hongxu; Jiang, Wei; Hao, Gazi
Abstract: This investigation was devoted to exploring the application performance of nano‐combustion catalyst CuCr2 O4 in solid propellants. In this paper, raw CuCr2 O4 and nano‐CuCr2 O4 prepared by the mechanical grinding method were applied in solid propellants containing ammonium perchlorate (AP), which are ammonium perchlorate/ hydroxy‐terminated polybutadiene propellant (AP/HTPB) and ammonium perchlorate/composite modified double‐base propellant (AP/CMDB). And the scanning electron microscope, displacement volume method, thermogravimetric analysis, differential scanning calorimetry, and strand burner method were employed to characterize the performance of AP‐based solid propellants. The results show that the AP/HTPB propellant has fewer defects on the surface of it due to the presence of nano‐CuCr2 O4, but it has no significant effect on the AP/CMDB propellant. Nano‐CuCr2 O4 can also significantly increase the density of AP/HTPB propellant and AP/CMDB propellant to 1.736 g/cm 3 and 1.633 g/cm 3, respectively. Nano‐CuCr2 O4 obviously advances the decomposition temperature of AP/HTPB propellant and AP/CMDB propellant, which also increases the apparent heat of decomposition. In addition, the burning rate of nano‐CuCr2 O4 ‐AP/HTPB propellant and nano‐CuCr2 O4 ‐AP/CMDB propellant increased to 1.60 mm/s and 3.23 mm/s, with an increase of 28.3 % and 26.3 %, respectively. Therefore, nano‐CuCr2 O4 is expected to be widely used in solid propellants due to its excellent properties. Abstract :